Meningkatkan Loyalitas Merek dari Kekuatan Citra Merek (Studi Kasus pada Nasabah Bank Mandiri Syari’ah di Kabupaten Cirebon) - Sahara Sahara (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
The research is highly in many different opinions among same expert about influence of brand image, customer value, and brand trust in establishing brand loyalty. Thus the aims of the research is to test the influence of the brand image to brand loyalty via customer value and brand loyalty. Researcher used strtuctural equation model with the AMOS 4.01 program to calculate the effect of each variable. A model will be developed to describe these relationship. This research was conducted in Cirebon with research object of Mandiri Islamic Bank. The data of this research from the 190 questionaires distributed, 140 were returned. The analysis finds that although brand image not directly affect brand loyalty, it does so indirectly via customer value, and brand trust. The result found that brand loyalty positively related to customer value and brand trust.